Modeling the effects of light wavelength on the growth of Nostoc ellipsosporum (2020)
Mathematical models provide information about population dynamics under different conditions. In the study, four models were evaluated and employed to describe the growth kinetics of Nostoc ellipsosporum with different light wavelengths: Baranyi-Roberts, Modified Gompertz, Modified Logistic, and Richards. N. ellipsosporum was grown in BG-11 liquid medium for 9 days, using 12 hours of photoperiod and the following treatments: white light (400-800 nm), red light (650-800 nm), yellow light (550-580 nm) and blue light (460-480 nm). Each experiment was performed in triplicate. The optical density (OD) was measured on days 1, 3, 5, 7 and 9, using a spectrophotometer at 650 nm. The maximum cell growth was obtained under white light (OD650 : 0.090 ± 0.008), followed by the yellow light (OD650 : 0.057 ± 0.004). Conversely, blue light showed a marked inhibitory effect on the growth of N. ellipsosporum (OD650 : 0.009 ± 0.001). The results revealed that the Baranyi-Roberts model had a better fit with the experimental data from N. ellipsosporum growth in all four treatments. The findings from this modeling study could be used in several biotechnological applications that require the production of N. ellipsosporum and its bioproducts.